Modes of regulation of casein kinase II. - Jakobi, R.; Lin, W.J.; Traugh, J.A. (Cellular and Molecular Biology Research, 1994)
Casein kinase II is unique when compared to other protein kinases; it utilizes GTP with almost the same effectiveness as ATP and exists as an active holoenzyme which does not need to be activated by dissociation of regulatory subunits or unfolding of regulatory domains. In vitro, the activity of casein kinase II is inhibited by acidic compounds and stimulated by basic compounds. Casein kinase II activity is inhibited by 2,3-bisphosphoglycerate and stimulated by polyamines at levels which are physiological in red cells. To examine the effects of autophosphorylation of the beta subunit on activity, two mutants of the Drosophila beta subunit have been constructed in which Ser-4 or Ser-(2-4) are changed to alanine residues. Analysis of autophosphorylation with wild-type and mutant recombinant holoenzymes reveals Ser-2 and Ser-3 as the major autophosphorylation sites. Autophosphorylation does not affect the phosphorylation of casein, but reduces the rate of phosphorylation of glycogen synthase by 30%, elongation factor I by 50-70%, and calmodulin by 20-40%. The data indicate that autophosphorylation of the beta subunit can negatively regulate the phosphotransferase activity of casein kinase II with physiological substrates. To examine regulation of casein kinase II activity by the beta subunit, recombinant alpha and beta subunits from human and Drosophila were expressed in Escherichia coli. Upon formation of the holoenzyme, the beta subunit stimulated the catalytic activity 4- to 5-fold. The catalytic alpha subunit contains the eleven conserved subdomains characteristic of all protein kinases.(ABSTRACT TRUNCATED AT 250 WORDS)